Urgensi Marketing Public Relations (MPR) dalam Membangun Brand Awareness di Era Digital - Mudawamah, Dewi; Sulistyowati (Al-Musthofa: Journal of Sharia Economics, 2024)
The purpose of this study is to analyze the differences between multi-level marketing (MLM) businesses and money games. This analysis is considered necessary due to the negative stigma in society that equates the MLM system with money games. The study also analyzes how MLM businesses can reposition themselves to eliminate this negative stigma. This research uses the Library Research method, which involves utilizing existing materials or data sources such as books, articles, scientific journals, reports, archives, and other documents available in libraries or other literature sources. The differences between Sharia-compliant MLM businesses and money games can be seen from several perspectives, including legal foundations and principles, sources of income, structure and sustainability, legality, and the risks for members. Steps to restore the positive image of MLM businesses can be taken through several measures, such as: engaging Public Relations (PR) to collaborate with parties who recommend that MLM businesses are haram, having stakeholders clarify to the public that there is a distinction between MLM businesses and money games, terminating employees found to be involved in money game practices, and changing the company's name and leadership if the company has already acquired a negative image.